Comparison of Two Indices of Availability of Fruits/Vegetable and Fast Food Outlets - Mercille, Geneviève (Springer US, 2012)
Studies of food environment often examine single dimensions of areas that may not account for complexity of exposure to all food sources. With respect to the deprivation amplification hypothesis, particular needs are to assess whether relative or absolute measures of the food environment are related to characteristics of social environment. The objective of this study was to compare absolute availability (AA) of fast food outlets (FFO) and stores selling fresh fruits and vegetables (FVS) with the relative availability (RA) of the same food sources in relation to area-level poverty and ethnic diversity in 248 selected census tracts (CT) in Montreal, Canada. AA of FFO and FVS were expressed as areal densities of food sources within CTs. RA indices were calculated as the proportion of FVSs relative to total food stores and the proportion of FFOs relative to all restaurants within CTs, respectively. Whereas the AA of FFO was positively associated with area-level poverty and ethnic diversity, the RA of FFO was inversely associated with area-level poverty and not associated with ethnic diversity. Both measures of FVS were positively associated with area-level poverty and ethnic diversity. These findings do not support a model of deprivation amplification. Furthermore, results of FFO suggest that the alternate measure of RA can complement information based on AA indicators of the food environment, with potential utility in predicting eating practices.